Inelastic electric and magnetic electron scattering form factors of 24Mg nucleus: Role of g factors - Al-Sammarrae, Anwer Ahmed; Inche Ibrahim, Mohd Lukman; Ahmeed Saeed, Muna; I. Sharrad, Fadhil (World Scientific, 2017)
The electric and magnetic transitions in the 24Mg nucleus are studied based on the calculations of the longitudinal and the transverse electron scattering form factors. The universal sd-shell model Hamiltonian (USDA) is used for calculations. The wave functions of radial single-particle matrix elements are calculated using the Skyrme potential. For the longitudinal form factors, a good agreement is obtained between the calculations and the experimental data. For the transverse form factors, the effective g factors are made as adjustable parameters in order to describe the experimental data.